Abundance and Distribution of Gastropoda in Intertidal Zone of Teluk Sikulo Beach of Pesisir Selatan Regency West Sumatera Province - Rosyidin, Hidayatul; Tanjung, Afrizal; Siregar, Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in September 2016 in the Teluk Sikulo Beach coastal area of the Pesisir Selatan Regency, West Sumatera Province, aimed to determine the distribution and abundance of gastropods in the intertidal zone. Gastropods samples were taken by using Quadrant Transect Sampling Method and sample was analyzed in Marine Biology Laboratory, Fisheries and Marine Sciences Faculty and data was investigated descriptively. Based on the research upper zone is a zone of its low abundance value of 0.67 ind / m² and lower zones with the highest abundance of 6.33 ind / m², Abundance of gastropods were found during the study on Teluk Sikulo varies, where the highest abundance of species of gastropods are Rhinoclavis vertagus found as many as 17 species and abundance lowest gastropods are 2 species was Cypraea Leviathan and Oliva sp.Keywords: Gastropods, Distribution, Abundance, Teluk Sikulo Beach, West Sumatera